2009
DOI: 10.1515/corrrev.2009.27.1-2.1
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of Microbiologically induced Corrosion of Metals in the Environments containing Sulphate-reducing Bacteria

Abstract: This review collates the research efforts that have contributed to better understanding of microbiologically induced corrosion (MIC). The important questions relating to the action of sulphate-reducing bacteria (SB) on metals, particularly iron and stainless steels, are considered: (1) the cathodic depolarization theory, (2) the corrosive metabolite theory, and, (3) the recently proposed mechanisms of MIC of ferrous metals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…The most commonly found iron sulfides produced along MIC are mackinawite and greigite, while they may be transformed into marcasite and pyrite over time (Jack et al, 1996;Little et al, 2000). It has been reported that marcasite is not stable under natural environmental conditions and therefore, its presence in the corrosion products may indicate that the corrosion is SRB-induced (Little et al, 2000;Vukovićet al, 2009).…”
Section: Corrosion Caused By Srbmentioning
confidence: 99%
“…The most commonly found iron sulfides produced along MIC are mackinawite and greigite, while they may be transformed into marcasite and pyrite over time (Jack et al, 1996;Little et al, 2000). It has been reported that marcasite is not stable under natural environmental conditions and therefore, its presence in the corrosion products may indicate that the corrosion is SRB-induced (Little et al, 2000;Vukovićet al, 2009).…”
Section: Corrosion Caused By Srbmentioning
confidence: 99%
“…Corrosion inhibition, arising from the presence and activities of bacteria within biofilms, has been reported for a number of metals and alloys, including carbon and stainless steels, 41À46 aluminum, 47,48 and copper. 49 However, the nature and formation of biofilms cannot be predicted with certainty and metal binding by extracellular materials has been reported as a mechanism for both biocorrosion 50,51 and corrosion inhibition. 33,50À52 Close to 90% of total corrosion prevention costs are spent on protective coatings, 53 and the use of protective coatings has also been a major strategy against biocorrosion since the 1980s.…”
Section: Microbiologically Influenced Corrosion (Mic) Of Metals and I...mentioning
confidence: 99%
“…Corrosion inhibition, arising from the presence and activities of bacteria within biofilms, has been reported for a number of metals and alloys, including carbon and stainless steels, aluminum, , and copper . However, the nature and formation of biofilms cannot be predicted with certainty and metal binding by extracellular materials has been reported as a mechanism for both biocorrosion , and corrosion inhibition. , …”
Section: Microbiologically Influenced Corrosion (Mic) Of Metals and I...mentioning
confidence: 99%
“…Since a number of metabolites and individual species may be involved in the microbial corrosion process, there are no examples of microbial corrosion that can be described by a single mechanism (Figs 8.10 and 8.11). Therefore, a much more detailed insight into microbial corrosion can be achieved by considering a variety of phenomena occurring at metal-medium-microorganism interfaces (Vukovic et al, 2009 cases, a localized, pitting-type of corrosion and (in soil environments, for example) the maximum corrosion rate of steel and iron by the action of SRB and/or APB is reported to be 0.7 mm/y to 7.4 mm/y (see Fig. 8.12) (Prichard, 1997).…”
Section: Carbon Steelmentioning
confidence: 99%